Skeletal allometries in the leopard tortoise (Stigmochelys pardalis): Predicting chelonian body size and mass distributions in archaeozoological assemblages. (20th March 2022) - Codron, Daryl; Holt, Sharon; Wilson, Beryl; Horwitz, Liora Kolska
Abstract: Establishing body mass from skeletal remains of an animal is of importance to researchers in the fields of ecology, palaeontology and archaeozoology. Establishing such standards requires that different body parts follow allometric growth curves, and that one can access a sufficiently large sample of individuals of known size and weight for the target species. Here, we have used data collected from modern living and dead leopard tortoises Stigmochelys pardalis (Bell, 1928), to reconstruct body size and mass from measurements taken on individual postcranial bones. The results show high correlations in both mass and size for various dimensions taken on most skeletal elements, enabling reconstruction of these parameters from individual skeletal measurements. To highlight the application of such data to fossil fauna, allometric equations derived from regression analyses of the modern animals were applied to a sample of Later Stone Age (ca. 10, 000 BP to present) leopard tortoise remains from Wonderwerk Cave located in the central interior of South Africa. Results for this archaeological sample show significant changes in size and body mass over time. These best correlate with shifts in paleoenvironmental conditions rather than with anthropogenic pressures that have commonly been implicated in size reduction or biased sex ratios in tortoise populations.